Use of open data in Ukraine: some important aspects - Shevchenko, Viktoriya (2020)
The article explores the open data phenomenon, data-driven analytics and special attention is given to the media industry where they act as raw materials for creating text, image or video content. The aim of scientific intelligence is to identify the principle of working with data in the public domain in Ukraine. Direct opportunities for analytics, access to public information are considered, classification features of data are revealed, social indicators are singled out and interpreted for society.